Chelonodontops bengalensis (Tetraodontiformes: Tetraodontidae): A New Species of Puffer Fish from the Northern Bay of Bengal Based on Morphology and DNA Barcode - Habib, Kazi Ahsan; Neogi, Amit Kumer; Oh, Jina; Lee, Youn-Ho; Kim, Choong-Gon (Ocean science journal, 2019)
The new puffer fish species Chelonodontops bengalensis (Pisces: Tetraodontidae) is described from two specimens collected on the southwest coast of the Bay of Bengal, Bangladesh. C. bengalensis is closely related to C. patoca (Hamilton, 1822), both species being large puffers with a peculiar, disc-shaped exposed nasal organ. The new species however differs from C. patoca with respect to dorsal rays (12 vs 10), anal rays (10 vs 8), pectoral rays (19 vs 15–16) and gill rakers (8 vs 7). C. bengalensis has spinules on its lateral sides but not on the caudal peduncle (vs. a patch of spinules on the back from behind the interorbital nearly to the dorsal fin and another on the throat and abdomen but absent on the lateral sides in C. patoca ). Both the DNA barcode region of the mitochondrial COI gene and 16S rRNA gene region of C. bengalensis showed a clear monophyletic clade that distinguishes it as a separate species in the phylogenetic tree from other closely related puffer fish species. The COI barcode region shows a genetic divergence of 6 to 7.6% between C. bengalensis and C. patoca reported in GenBank from different parts of Asia.